Endometriosis and Infertility: A Systematic Review. Issue 3 (July 2017) - Harris, Amani; Tsaltas, Jim
Endometriosis is one of the most common gynaecological conditions affecting 6% to 12% of women in the reproductive age group. It can be found in 35% to 45% of women who are trying to conceive and are infertile. Infertility is one of the most common problems associated with endometriosis. This review will look at the evidence that endometriosis may lead to infertility and the data looking at whether surgical correction of endometriosis may improve fertility outcomes.